PENGEMBANGAN PRODUK JELLY DRINK TEMULAWAK (Curcuma xanthorrhiza Roxb.) SEBAGAI PANGAN FUNGSIONAL - Hartati, Fadjar Kurnia; Djauhari, Arlin Besari (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2017)
People still consider the curcumin as a herb that has a taste and smell that is less preferred so as to increase consumption of ginger need to be diversified more modern products, one of which is jelly drink. Success in the manufacture of jelly drinks is determined by the concentration of gelling agents. The objective of the research was to determine the effect of carrageenan and sugar concentration on the physical and organoleptic properties of jelly drink curcumin, looking for the best treatment, which was then best tested for curcumin, total phenol and antioxidant activity to ensure that the product was potential as one of functional food products. With Randomized Block Design (RAK) method 2 factors, namely the concentration of carrageenan (K) and sugar (G), each consisting of 3 levels and repeated 4 times so that there are 36 samples. The results showed that the average total soluble solids ranged from 10.5 to 17.2 o Brix, the mean of sineresis ranged from 5.11 to 7.16% and the mean suction rate ranged from 28.17 to 49.05 seconds / 50 ml. The best treatment was found in combination treatment of 1% carrageenan and 10% sugar (K3G1) containing curcuminoid 1,2415%, phenol jelly drink curcumin 2,2659 mg GAE / g sample and IC50 value of 73 ppm. Keywords: curcumin, carrageenan, jelly drink, antioxidant